IMPLEMENTATION OF THE METHOD FOR RECITING THE QUR'AN BEAUTIFULLY USING VARIOUS RHYTHMIC TUNES (NAGHAM) - Arifah, Novie; Fakhri, Ahmad Fizal (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
Reciting the Quran beautifully is strongly encouraged among readers. This practice is supported by hadith and the scholarly consensus that emphasizes adorning one's recitation with a pleasing voice. By beautifying the recitation, it is believed to bring peace and joy to both the reciter and the listener. This study employs a literature review to compile existing research and explore novel perspectives on enhancing the beauty of Quranic recitation through various melodies (nagham) in contemporary contexts. The findings of this research are anticipated to contribute new insights into the art of Quranic recitation, offering a more enjoyable and fulfilling experience for both reciters and listeners. Keywords: Methods for melodic Quran recitation, Different types of musical rhythms